PERSPECTIVES FOR EARTHQUAKE PREDICTION IN THE MEDITERRANEAN AND CONTRIBUTION OF GEOLOGICAL OBSERVATIONS - Papazachos B.C.; Karakaisis G.F.; Papazachos C.B.; Scordilis E.M. (My University, 2006)
Accelerating seismic strain caused by the generation of intermediate-magnitude preshocks in a broad (critical) region, accompanied by decelerating seismic strain caused by the generation of smaller preshocks in the seismogenic region are systematically observed before strong mainshocks. On the basis of this seismicity pattern a model has been developed that seems promising for intermediate-term earthquake prediction, called the 'Decelerating in-Accelerating out Seismic Strain Model'. Recent seismological data for the Mediterranean region are used here for backward and forward testing of this model. The selection of the broader Mediterranean region as a test area was motivated not only by the interest of time-dependent seismic hazard assessment in a high-seismicity and highly populated region but also by the fact that the Mediterranean is a natural geophysical and geological laboratory where both complex multi-plate and continuum tectonics are found in a more or less convergent zone. Within this complex geotectonic setting several geological phenomena such as subduction, collision, orogen collapse and back-arc extension take place, leading to the generation of a broad spectrum of mainshocks, reaching Mw=8.0 or greater for subduction-related thrust events and a variety of corresponding seismicity levels and neotectonic activity ranging from very low (e.g. large parts of Iberian peninsula) to very high (broader Aegean area). The backward procedure shows that all six strong (M ≥ 6.8) mainshocks that have occurred in the Mediterranean since 1980 had been preceded by preshock sequences that followed this seismicity pattern and satisfy all model constraints. Application of the model for future mainshocks has led to the identification of nine regions (in the Pyrenees, Calabria, NE Adriatic, Albania, Northern Greece, SE Aegean, NW Anatolia, western Anatolia, NE Anatolia) where current intermediate-magnitude seismicity satisfies the constraints of the model and corresponds to strong (M ≥ 6.2) mainshocks. The magnitudes, epicentres and origin times of these probably ensuing mainshocks, as well as their corresponding uncertainties, are estimated, so that it is possible to evaluate the model potential during the next decade (2006-2015). Furthermore, it is shown that geological observations of surface fault traces can contribute to the accurate location of the foci of future strong mainshocks in the Mediterranean and to an estimation of their sizes. For this purpose, globally valid relations between fault parameters based on geological observations (surface fault length, Ls, and fault slip, us) and measures of mainshock size (mainshock magnitude, subsurface fault length, L, and fault slip, u) are proposed. © The Geological Society of London 2006.